2017
DOI: 10.1007/s12205-017-0960-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freeze-thaw cycles on triaxial strength properties of fiber-reinforced clayey soil

Abstract: Understanding effect of freezing phenomenon in a fiber-reinforced soil structure is essential to foundation technology, road construction and earthwork application in cold region. This research aims to present the results of experimental investigation relative to the unconsolidated-undrained triaxial compression behavior of fine-grained soil as a function of freeze-thaw cycles and fiber volume fractions. All measurements were carried out for 3 selected glass and basalt fiber fractions (0%, 0.5%, and 1%) and 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…Large numbers of experimental results have shown that the shear strength of soils generally decreases after freeze-thaw cycling, the degree of which depends on external factors such as moisture content [9] and dry density values [10]. Thus, the particular character of soil should also be concerned with, e.g., the surcharge loads [11] and fiber volume fractions [12]. To gain a further understanding of the effect of freeze-thaw weathering on the damage to soil or rock, many scholars have analyzed the freeze-thaw induced damage from the perspective of fracture energy [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Large numbers of experimental results have shown that the shear strength of soils generally decreases after freeze-thaw cycling, the degree of which depends on external factors such as moisture content [9] and dry density values [10]. Thus, the particular character of soil should also be concerned with, e.g., the surcharge loads [11] and fiber volume fractions [12]. To gain a further understanding of the effect of freeze-thaw weathering on the damage to soil or rock, many scholars have analyzed the freeze-thaw induced damage from the perspective of fracture energy [13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…This could help to reduce the effect of a freeze-thaw cycle on the soil. Relevant tests confirmed that the attenuation of elastic modulus, cohesion and internal friction angle induced by a freeze-thaw cycle can be inhibited by the treatment of short glass fibers [ 86 ]. Moreover, short glass fiber could also increase the shear modulus and damping ratio of the treated soil [ 87 ].…”
Section: Unconventional Materials Used In Soil Improvementmentioning
confidence: 99%
“…The deteriorations caused by freeze-thawing cycles for Ecolan-stabilized quarry fines were more serious, which resulted in a decrease in the UCS by about 20%. Yet, this amount of deterioration in the UCS is normal for stabilized granular materials such as lime-treated kaolinite [41,42] and fiber-reinforced clay [43,44]. However, improvement is still necessary to enhance the freeze-thawing resistance for quarry fines stabilized with fly ash, even though the ratio is right on the limit set by Finnish guidelines of 6.7 [18].…”
Section: Characterization Of Stabilized Quarry Fines As Constructimentioning
confidence: 99%